Major dietary patterns and their associations with diet quality indices in Iranian adults - Haghighatdoost, Fahimeh; Rashidi Pour Fard, Nafiseh; Karimi, Majid; Baghaei, Mohammad Hassan; Azadbakht, Leila (Progress in Nutrition, 2018)
Background: Limited data on the association of dietary patterns with nutrient intakes and diet quality indices are available. Objective: We examined the relation of dietary patterns and diet quality indices and nutrient intakes among Iranian. Methods: This cross-sectional study was conducted among 389 Isfahani adults. Dietary intakes were estimated using a validated semi-quantitative food frequency questionnaire. Dietary patterns were identified using factor analysis method. Diet quality indices [nutrient adequacy ratio (NAR), Mediterranean (MED) score, healthy eating index (HEI), dietary diversity score (DDS) and dietary energy density (DED)] were calculated according to standard methods. Results: We identified four dietary patterns: healthy, high animal fat and protein, traditional and Western patterns. Participants in the top tertile of healthy dietary pattern, in comparison with those in the first tertile, had greater NARs for all nutrients of concern, HEI (73.5±6.8 vs.67.7±6.3; P<0.0001) and MED score (5.5±1.2 vs. 3.5±1.5; P<0.0001). Higher scores of high animal fat and protein dietary pattern were more nutrient-dense, while greater adherence to the traditional dietary pattern was associated with greater MED score (4.8±1.5 vs. 4.2±1.7; P=0.004), but lower NARs. Individuals in the top tertile of Western dietary pattern had more energy-dense diet than those in the first (0.9±0.2 vs. 0.8±0.1; P=0.002) Conclusion: Dietary patterns are differently related to nutrient intakes and diet quality indices. Further studies are needed to determine the quality of dietary patterns to determine the best pattern.